Synthesis and Characterization of Cellulose Acetate Membrane from Cotton Spinning Waste - Djayanti, Silvy; Kusumastuti, Syarifa Arum; Fatkhurrahman, Januar; Purwanto, Agus; Budiarto, Agung; Suherman, Alex Lukmanto (UI Scholars Hub, 2021)
Cellulose acetate membrane (CAM) was successfully synthesized and characterized from the cotton spinning waste of the textile industry. The membrane was produced through the isolation, acetylation, and phase inversion stages. The highest yields of cellulose fiber and α-cellulose contents were obtained using 3.0% and 6.0% v/v NaClO, respectively. The C–O acetyl bond detected by Fourier Transform Infrared (FTIR) analysis indicates the formation of the CAM. The resulting membrane can be potentially applied as an ultrafiltration membrane for water desalination purposes in water and wastewater treatment facilities. Furthermore, the utilization of cotton spinning waste as raw material aims to produce inexpensive products and recycle solid waste from the textile industry.